Get your private garbage collector - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
A few issues ago (More with worms, see Spore 90, page 9) we carried an article on raising worms. One can, besides feeding them to animals, also use them for compost making. Also, one can get rid of 3 kilos of garbage weekly. Take a shallow plastic...